DNA Barcoding of Neolissochilus sumatranus and Tor douronensis to Support In Situ Conservation of Indonesian Mahseers - Sekar Larashati; Novi Mayasari; Yuli S Fitriana; Gema Wahyudewantoro; Mey R Widoretno; Tri Widiyanto (HAYATI Journal of Biosciences, 2022)
The fishes of genera Neolissochilus and Tor are locally known as Ikan Batak or ihan in North Sumatra. They are sacred and are usually served in Batak tribe traditional ceremonies. However, their population in the wild is declining because of habitat degradation, unwise exploitation, water pollution, and the introduction of invasive species. Therefore, suitable management is needed to maintain Ikan Batak's sustainability in their natural habitat, which can be conducted through in situ conservation. The habitat of Ikan Batak in the Bonan Dolok river of the Samosir Regency can potentially be developed as a conservation site. Information concerning this species in Bonan Dolok River is needed as a basis for effective in situ conservation management. Morphologically identified fish captured in Bonan Dolok River were validated using DNA barcoding of cytochrome oxidase I (COI) mitochondrial DNA segment. This study confirmed that Ikan Batak captured from Bonan Dolok River belongs to two genera, Neolissochilus and Tor. Furthermore, the phylogenetic tree construction using Maximum Likelihood showed that the specimens identified as N. sumatranus were identical to N. cf soroides, a species found in the Malaysian peninsula, Thailand, and Cambodia.